Analisis Faktor yang Berhubungan dengan Pemberian Asi Ekslusif Pada Bayi Usia 7-12 Bulan di Praktik Mandiri Bidan Fauziah Palembang Tahun 2021 - Ayu Hamdhani Ari Putri; Rizki Amalia; Satra Yunola (Universitas Batanghari Jambi, 2022)
Exclusive breastfeeding is the behavior of giving only breast milk from infants aged 0 to 6 months without any additional food or drink. Throughout the world there has been no achievement of the target of exclusive breastfeeding in accordance with the program that is being echoed. Only 36% worldwide and no more than 46% in ASEAN in the period 2007-2014. The study was conducted to see the relationship between knowledge, family support, and support from health workers with exclusive breastfeeding at PMB Fauziah in 2021. Analytical Survey Research with Cross Sectional. 38 mothers who had babies aged 7-12 months were used as the population and samples were taken by accidental sampling. Analysis using Chi Square. From 38 samples studied, it was found that there was a relationship between knowledge (P-value = 0.003), family support (P-value = 0.02) and support from health workers (P-value = 0.01) with exclusive breastfeeding. In conclusion, it was found that there was a significant relationship between knowledge, family support, and support from health workers with exclusive breastfeeding at PMB Fauziah Palembang. The results of this study can be used as input and information for midwives in an effort to improve health education and services, especially the exclusive breastfeeding program.